Incorporating equity into transportation plans: the case of pedestrian master plans - Berg, Amber (Kansas State University, 2020)
Equity is a long-recognized concern within the transportation sector, but there are no requirements for municipalities to address equity and no clear guidance for how to do so. This paper reviews fifteen pedestrian master plans to assess the equity considerations and to derive a tripartite framework for systematically incorporating equity into transportation plans: The Three A’s of Equity. This framework consists of Acknowledgement, the recognition of equity as a value; Accountability, the establishment of a commitment to advance equity; and Application, the steps to move toward equity. The research evaluates the existing plans using the proposed framework and finds that cities inconsistently incorporate equity into pedestrian plans, seldom include Accountability, and rarely include race in their equity considerations. The application of the Three A’s of Equity is not restricted to PMPs and is recommended for all transportation plan types to thoroughly incorporate equity and influence more equitable plan outcomes.
Incorporating equity into pedestrian master plans
Keywords: Equity; Pedestrian master plan; Transportation plan; Disparities; Municipal plan; Project prioritization